Caracterização parcial da peroxidade dos frutos de aceroleira (Malphigia emarginta DC), clones Okinawa e Emepa em três estágios de maturação - Sousa, Tatyana Patrício de Albuquerque (2010)
Acerola is a tropical fruit of economic and nutrition potential, considering its high vitamin content C. During the ripeness processes including chemical and biochemical enzymatic activities. The peroxidase (POD) and polyphenoloxidase (PPO) have been considered the main enzymes responsible for deterioration of quality in many fruits.The aim of this study was to determine enzymatic activity and some properties of peroxidase in the clones of acerola Okinawa and Emepa in three stages of maturation.In both clones the enzymatic activity (U) and specific activity (AE) were determined. Only the clone Okinawa were also determined pH and temperature optima and thermal stability of POD, by climate issues no availability of fruits Emepa clone. Data were subjected to descriptive statistics, normality test followed by ANOVA and t-Student test, completing the analysis of response surface in the pH and temperature optima and thermal stability. It was observed that POD and AE Units were higher (p<0.05) in clone Okinawa in relation to Emepa at all stages of maturation. In surface analysis, peroxidase showed maximum activity in phosphate buffer pH = 6.5 at T= 45°C. In studies of stability and thermal inactivation, there was marked loss of activity with increasing time and temperature.The total inactivation was not achieved, suggesting the presence of heat resistant isoenzymes, however 50% of maximum activity was achieved at 80°C and 4minute. After 24 hours of rest of the enzyme, recovery of enzymatic activity was observed at 90 ° C in all treatments. At 80°C decreased the activity of peroxidase, showing modest recovery in the shorter treatments. At 70°C there was no recovery of peroxidase. Such information is a prerequisite for new technologies that can prolong the shelf life of fruits